Brachyspira hyodysenteriae and B. pilosicoli Proteins Recognized by Sera of Challenged Pigs - Casas, Vanessa; Rodríguez-Asiain, Arantza; Pinto-Llorente, Roberto; Vadillo, Santiago; Carrascal, Montserrat; Abian, Joaquin (Frontiers in Microbiology, 2017)
The spirochetes Brachyspira hyodysenteriae and B. pilosicoli are pig intestinal pathogens that are the causative agents of swine dysentery (SD) and porcine intestinal spirochaetosis (PIS), respectively. Although some inactivated bacterin and recombinant vaccines have been explored as prophylactic treatments against these species, no effective vaccine is yet available. Immunoproteomics approaches hold the potential for the identification of new, suitable candidates for subunit vaccines against SD and PIS. These strategies take into account the gene products actually expressed and present in the cells, and thus susceptible of being targets of immune recognition. In this context, we have analysed the immunogenic pattern of two B. pilosicoli porcine isolates (the Spanish farm isolate OLA-9 and the commercial P/43/6/78 strain) and one B. hyodysenteriae isolate (the Spanish farm V1). The proteins from the Brachyspira lysates were fractionated by preparative isoelectric focusing, and the fractions were analysed by Western blots with hyperimmune sera from challenged pigs. Of the 28 challenge-specific immunoreactive bands detected, 21 were identified as single proteins by MS, while the other 7 were shown to contain several major proteins. None of these proteins were detected in the control immunoreactive bands. The proteins identified included 11 from B. hyodysenteriae and 27 from the two B. pilosicoli strains. Eight proteins were common to the B. pilosicoli strains (i.e., elongation factor G, aspartyl-tRNA synthase, biotin lipoyl, TmpB outer membrane protein, flagellar protein FlaA, enolase, PEPCK and VspD), and enolase and PEPCK were common to both species. Many of the identified proteins were flagellar proteins or predicted to be located on the cell surface and some of them had been previously described as antigenic or as bacterial virulence factors. Here we report on the identification and semiquantitative data of these immunoreactive proteins which constitute a unique antigen collection from these bacteria.